Impact assessment of HIV/AIDS knowledge and prevention among patrons of bars and hotels in Abuja, Nigeria (2009)
The Federal Capital Territory (FCIJ Abuja, is notable for its increasing population and convergence of peoples and cultures. This high volume of in-migration into the FCT exerts a considerable pressure on the economic and social life of its inhabitants. Understandably, bar/hotel business ranks among the most patronized ventures in the city as a result of multiple government, academic/research and nongovernment engagements and attendant activities of sex workers who visit such bars and hotels. As a result of the number of people that have stake either as proprietors or patrons and the centrality of these business outfits to the understanding of events in the city, selected bars and hotels were chosen for this impact study on HIVIAIDS-knowledge and prevention. The main objective of this study is to assess the impact of various HIVIAIDS intervention programmes on the knowledge and attitudes of patrons of bars and hotels in the FCT towards HIVIAIDS and adoption of preventive methods through exposure to different prevention strategies. Data for this study were collected at two levels through: (1) a pre-intervention baseline survey; and (2) post-intervention questionnaires. In this way, the level of the effects of the AIDS-education programme on respondents' knowledge and attitude to HIVIAIDS prevention measures was highlighted. The findings show clearly that multiple socioeconomic and cultural factors influence patronage of bars and hotels in the FCT; and the intervention impacted positively on respondents' knowledge of HIVIAIDS, as well as condom use.